2018
DOI: 10.1103/physrevc.97.014607
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of complete and incomplete fusion in the Li7+Sn124 reaction near Coulomb barrier energies

Abstract: The complete and incomplete fusion cross sections for 7 Li+ 124 Sn reaction were measured using online and offline characteristic γ-ray detection techniques. The complete fusion (CF) cross sections at energies above the Coulomb barrier were found to be suppressed by ∼ 26 % compared to the coupled channel calculations. This suppression observed in complete fusion cross sections is found to be commensurate with the measured total incomplete fusion (ICF) cross sections. There is a distinct feature observed in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…In the studies of fusion with WBPs, the complete fusion (CF) cross sections are found to be suppressed at above barrier energies with respect to predictions of onedimensional barrier penetration model (1DBPM) [1,2]. An interesting observation in these measurements is that the amount of suppression is commensurate with the measured incomplete fusion (ICF) [6,7]. Total fusion * vparkar@barc.gov.in (TF) which is sum of CF and ICF cross sections match with the 1DBPM predictions at above barrier energies [2].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In the studies of fusion with WBPs, the complete fusion (CF) cross sections are found to be suppressed at above barrier energies with respect to predictions of onedimensional barrier penetration model (1DBPM) [1,2]. An interesting observation in these measurements is that the amount of suppression is commensurate with the measured incomplete fusion (ICF) [6,7]. Total fusion * vparkar@barc.gov.in (TF) which is sum of CF and ICF cross sections match with the 1DBPM predictions at above barrier energies [2].…”
Section: Introductionmentioning
confidence: 91%
“…The single particle states along with Spectroscopic factors (C 2 S) considered in the calculations are given in Table II. For the 7 Li → 6 Li+n transfer, both the 1p 3/2 and 1p 1/2 components of the neutron bound to 6 Li were included with spectroscopic factors of C 2 S = 0.43 and 0.29 respectively, taken from Cohen and Kurath [28]. Similarly for 7 Li+n → 8 Li transfer, both the 1p 3/2 and 1p 1/2 components of the neutron bound to 7 Li were included with spectroscopic factors of C 2 S = 0.98 and 0.056 respectively, taken from Cohen and Kurath [28].…”
Section: A Crc Calculationsmentioning
confidence: 99%
See 3 more Smart Citations